Total Incapacitation: Colonial-style Counter-insurgency Policing in the Repression of the Protests in Solidarity with Palestine in Germany - della Porta, Donatella (PARTECIPAZIONE E CONFLITTO, 2026)
This article conceptualises total incapacitation policing as a counter-insurgence strategy oriented towards the denial of protest rights to groups that are stigmatized as being extremist because opposed to the dominant raison d’État which claim moral superiority in the defence of Israeli security. In order to understand the development of a police strategy of total incapacitation, the analysis aims to fill a gap in social movement studies on repression in Western democracy by starting a dialogue with historical and contemporary analysis of the continuous impact of colonialism in its different forms. In fact, the strategy of total incapacitation is to be connected with a return to the metropolis of forms of colonial policing against the protests by the colonised subject, which go well beyond the policing of protest in the streets. The article first addresses the theoretical approach and methods used, introducing then some general characteristics of the policing of protests in solidarity with Palestine in Germany and then analyse in depth the case of the Palestine Congress looking at the specific strategy of total incapacitation, based upon the denial of the right to protest, the intimidation of protestors in their direct interactions with the police as well as forms of disinformation and stereotyping. It will then attempt to explain the emergence of this strategic incapacitation style of protest policing by looking at the internal characteristics of the police as well as the direct and indirect demands placed upon it by the government and the mobilization of a powerful law and order coalition.